Optimal targeting under budget constraints in a humanitarian context. (July 2019) - Verme, Paolo; Gigliarano, Chiara
Highlights: The paper proposes to use ROC curves to refine targeting of cash programs. It shows how to find probability thresholds that optimize coverage and leakage rates. It provides simple graphical devices designed for policy makers to take decisions on targeting. Abstract: The paper uses Receiver Operating Characteristic (ROC) curves and related indexes to determine the optimal targeting strategy of a food voucher program for refugees. Estimations focus on the 2014 food voucher administered by the World Food Program to Syrian refugees in Jordan using data collected by the United Nations High Commissioner for Refugees. The paper shows how to use ROC curves to optimize targeting using coverage rates, budgets, or poverty lines as guiding principles to increase the overall efficiency of a program. As humanitarian organizations operate under increasing budget constraints and increasing demands for efficiency, the proposed approach addresses both concerns.